Validation of Schwartz’s Human Values Scale in Spanish Children - José L. Álvaro; Elena Pascual Sánchez; Khalil da Costa Silva; Ana R. Torres; Alicia Garrido; Miryam Rodríguez (Psicología Educativa: Revista de los Psicólogos de la Educación)

(untitled)
The research aimed to analyze the validity of the Picture Based Value Survey for Children (PBVS-C) following the Schwartz’s model of values in a sample of 411 Spanish children (207 boys and 204 girls). Multidimensional scaling (MDS) was carried out and the results obtained revealed the replicability of the proposed model in the Spanish population. In addition, differences were verified in terms of sex and age. Participants under ten years old scored higher in the values of self-transcendence, openness to change, and conservation. The sex of the participants, in turn, showed differences in the dimensions of self-transcendence and self-enhancement; boys scored higher in the values of self-enhancement while girls scored higher in the values of self-transcendence.